Sensory trail planning at Ayer Hitam Forest Reserve, Puchong - Sharfudin, Fathin Nabilah (2018)
There are many elements of natural resources with high potential that can be used as sensory stimulator elements along the sensory trail in Ayer Hitam Forest Reserve area. This study was conducted to plan for a sensory trail that can be used as therapeutic recreational activities for low vision and blind people at AHFR. The planning was to establish a sensory element on the existing forest trail that can benefit low vision and blind people to experience outdoor activities in a forest area. A recreation resource inventory was conducted in the sampling point’s interval of 10 m (metres) distance, to evaluate and identify the recreation resources that can be translated into sensory trail; soil, water, flora and fauna, meteorology and the trail surrounding. Two proposed routes were accessed and as a result trail A was selected. The study showed that the selected route is suitable for a sensory trail that can enhance the quality of outdoor recreation activities for low vision and blind people.